Impact of the Court Process on Sexually Abused Children in North Carolina, 1983-1986 - Runyan, Desmond K. ([Verlag nicht ermittelbar], 1993)
This data collection examines the psychological impact of judicial processes on child sexual abuse victims. More specifically, it provides information on how sexual abuse and the subsequent judicial processes affect the mental health functioning of child victims by assessing the impact of (1) additional harm to victims from out-of-home placement, (2) criminal prosecution of the offender/family member, (3) subject testimony in juvenile or criminal court, and (4) family and professional support for the children. Children were enrolled in the study at the time that social services personnel substantiated claims of sexual abuse, and they were followed for a period of 18 months. Assessments of the mental health functioning of the children were made at the time of initial investigation, five months later, and 18 months later, using a combination of self-reports, parent and teacher reports, and psychological tests. After obtaining informed consent from the parent or guardian, each child was interviewed using a structured psychiatric inventory. The specific impacts of the various judicial processes or interventions under study were examined through comparisons of subgroups of the sample that did and did not experience particular interventions. The interventions included social services investigation, court process, foster placement, and psychological therapy. Other information in the file includes the type of sexual abuse experienced, judicial interventions the child experienced, and the child's level of depression, anxiety, and social adjustment. Demographic variables include age, sex, and race.